Phylogenetic Relationships in the Miracle Berry Genus, Synsepalum, Sensu Lato, and Relatives (Sapotaceae) - Daniel Potter; Mark Uleh (Plants)
Synsepalum and Englerophytum are two closely related genera of the sub-family Chrysophylloideae in the family Sapotaceae. It has been reported that the two genera are a monophyletic group, and their generic limitations are uncertain. Synsepalum is an economically important genus that includes the medicinally and culinarily important plant, -miracle berry, S. dulcificum. The phylogenetic relationships among the species are poorly understood. This study has been conducted to refine the phylogenetic relationships between and within the two genera utilizing nuclear and chloroplast DNA data. Bayesian analyses and Maximum likelihood of nuclear internal transcribed spacer (ITS) and plastid (trnH-psbA) sequences were used to reconstruct the phylogeny of the two genera. Phylogenetic trees generated for both regions (nuclear and plastid) resulted in the resolution of six clades. Four of the clades correspond to species in the genus Synsepalum and two clades include species of Englerophytum. The two clades of Englerophytum are nested within Synsepalum suggesting that the two genera are closely related and may not merit their current circumscription as distinct genera. Also, Synsepalum is confirmed to constitute more than one lineage suggesting it is not monophyletic in its current definition. Overall, the study suggests the need for a comprehensive evaluation of all species currently recognized in the two genera.